Transverse energy propagation and interference of elliptical Gaussian beams - Li, Jin; Tan, Shuang-cheng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Elliptical Gaussian beam (EGB) has many different physical properties from circular Gaussian beam. In this paper, the transverse energy flux and intensity of one and two coherent EGBs are studied. In our simulation, the transverse energy flux and intensity varying with waist ratio are discussed in detail. It has been found that through increasing the waist ratio, the transverse energy flux after interference would be strengthened significantly. Although the transverse energy flux is much weaker than the longitudinal energy flux, its signal to noise ratio has been verified to be strong enough for detection. Our derivations are still reasonable for another simulation with general experimental parameters. The simulation results are considered to be helpful for some physical experiments using the transverse energy flux of Gaussian beam, such as an important application in electromagnetic response produced by interaction of high-frequency gravitational waves.
Optica Applicata, Vol. 53, 2023, nr 2, s. 249-260
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; elliptical Gaussian beam; transverse energy flux; interference of EGBs